2020
DOI: 10.1038/s41419-020-2725-4
|View full text |Cite
|
Sign up to set email alerts
|

Twist-mediated PAR1 induction is required for breast cancer progression and metastasis by inhibiting Hippo pathway

Abstract: Breast cancer is considered to be the most prevalent cancer in women worldwide, and metastasis is the primary cause of death. Protease-activated receptor 1 (PAR1) is a GPCR family member involved in the invasive and metastatic processes of cancer cells. However, the functions and underlying mechanisms of PAR1 in breast cancer remain unclear. In this study, we found that PAR1 is highly expressed in high invasive breast cancer cells, and predicts poor prognosis in ER-negative and high-grade breast cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Moreover, YAP forms a TEAD/YAP/AP1 ternary complex to regulate activity of distal enhancers, whereas ZEB1 and YAP are part of a multimeric complex with AP1 factors independent of direct ZEB1 DNA binding to drive gene expression on a genome‐wide level (Zanconato et al , 2015 ; Feldker et al , 2020 ) (Fig 4B ). Wang and colleagues demonstrated that in breast cancer, also TWIST is involved in YAP/TAZ‐mediated EMT orchestrated by TWIST‐dependent activation of the GPCR member PAR1 (Wang et al , 2020 ).…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
“…Moreover, YAP forms a TEAD/YAP/AP1 ternary complex to regulate activity of distal enhancers, whereas ZEB1 and YAP are part of a multimeric complex with AP1 factors independent of direct ZEB1 DNA binding to drive gene expression on a genome‐wide level (Zanconato et al , 2015 ; Feldker et al , 2020 ) (Fig 4B ). Wang and colleagues demonstrated that in breast cancer, also TWIST is involved in YAP/TAZ‐mediated EMT orchestrated by TWIST‐dependent activation of the GPCR member PAR1 (Wang et al , 2020 ).…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
“…In agreement, breast cancer TF/F3 is an independent prognostic factor for overall survival and has a predictive value for distant metastasis [ 52 ]. Moreover, previous pilot studies have suggested that PAR1 is upregulated in aggressive breast cancer [ 53 , 54 ], and mechanistic studies have demonstrated that PAR1 induction promotes breast cancer progression and metastasis [ 55 ]. PAR2 is highly expressed in infiltrative ductal breast cancer tissue [ 56 ] and has been shown to be associated with distant disease-free survival in a previous study on 221 breast cancer patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In gastric and CRC cells, PAR-1 activation leads to upregulation of pro-EMT transcriptional factor Snail and Twist, respectively [ 28 , 67 ]. PAR-1 is also involved in the activation of YAP/TAZ [ 64 , 65 ]. Inhibition of PAR-1 suppresses YAP/TAZ-induced EMT, invasion, migration, cancer stem cell-like properties, tumour growth and metastasis of breast cancer cells [ 65 ].…”
Section: Discussionmentioning
confidence: 99%